Multilingual Landscape Of Khyber Pakhtunkhwa And Manifestation Of Writing System Mimicry (Journal of Namibian Studies : History Politics Culture, 2023)
he linguistic landscape (e.g., signboards & billboards) displays disparity between the selection of lexical forms, writing systems, and scripts. Therefore, this research intends to explore different patterns of writing system mimicry that appear in the multilingual landscape of Mardan and Nowshera districts, Khyber Pakhtunkhwa (KPK) Pakistan. A qualitative and quantitative analysis of purposively selected 686 photographs were conducted. The study has uncovered four patterns of writing system mimicry, including English in the abjad writing system, Urdu in the alphabetic writing system, Pashto in the alphabetic writing system, and mixed writing systems. This mimicry leads to the death of a language and its writing system. Additionally, these four patterns are compared statistically. The results reveal that signs are chock-full of abjad-written English terms. It connotes that local people are aware of English vocabulary but are unfamiliar with the script. This discrepancy between the writing system (script) and vocabulary selection affirms either a lack of national and regional languages’ linguistic knowledge or a personal inclination toward English. It symbolizes English imperialism in Pakistan. The study validates the assumption that English is the linguistic capital, as linguistic landscape actors prefer to employ it with a local flavor.